Central African Economic and Monetary Community : Common Policies in Support of Member Countries Reform Programs-Staff Report, and Statement by the Executive Director. (IMF Staff Country Reports; Country Report, 2022)
CEMAC ended 2021 in a fragile external position, with gross reserves at only 2.7 months of prospective imports and net foreign assets (NFA) at their lowest level in decades, despite the availability of Fund financing, the SDR allocation, and monetary policy tightening. The terms of trade shock this year is expected to be broadly positive for CEMAC. This more favorable outlook is, however, subject to heightened external uncertainties associated with the fallout from the war in Ukraine (notably global inflation pressure, global growth uncertainties, and high oil price volatility), faster-than-anticipated global financial tightening, possible emergence of new COVID strains and risks from cryptoassets. Current high oil prices, if sustained, will help rebuild fiscal and external buffers, provided fiscal policies remain prudent. Shielding vulnerable populations from soaring energy and food prices adds to the complexity of navigating this uncertain environment, given CEMAC's already limited policy options.